Aplikasi Sistem Pengendali dan Manajemen Penjadwal Peralatan Listrik dalam Ruangan - Firdausi, Aulia Latifah Insan; Sumardi, Sumardi; Christyono, Yuli (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Energy crisis is one of the facing globalization problems, and the behavior of energy users like the carelessness in turning the electrical devices on or off are the most significant factor in energy consumption. Therefore, in this final project is made a system for controlling and managing the electrical devices in order to use appropriately needed. This system consists of two main parts, hardware and application. Hardware consists of a master station as the central sending command and two slave stations to execute the sending command. Application will provide information sent to the hardware. Both parts of systems are built with Delphi programming language and MySQL for keeping the database. And the communication between hardware and application use Wireless ZigBee (XBee-PRO) module. This final project results a system for controlling and managing electrical devices based on database to raise the user efficiency. The results show that system can optimize energy consumption and the available technical data information well organized as appropriate as needed. And Wireless ZigBee (XBee-PRO) modules used as communication media between hardware and application have communication range over than 200 meters outdoor and 90 meters in indoor.Â Keyword :Â Â Controlling and managing application, ZigBee-PRO, database scheduled, Delphi 7.0